(untitled) (Applied Biological Research, 2020)
The mid-day meal scheme began in India with thgoal to eradicate hunger for millions of children and to contribute to their education, nutrition and health. However, it has not achieved the goal at the desired pace to meet the Millennium Development Goals. This study was conducted in 11 government schools of Khamanon block of district Fatehgarh Sahib, Punjab (India). It is a cross sectional study in which the sample size of 336 was alculated based on the prevalence of malnutrition. The hidden, quasi hidden and sensory attributes of food served under mid-day meal scheme in Khamanon block were examined. The results revealed that uric acid levels were above the PFA standards for wheat and rice (>1%) while aflatoxins levels were within the permissible limits. Less than 10% weevil infestation was observed in wheat, rice and green gram, one week after storage. There were no rodent infestations in food grains. Broken count of food grains was < 10%. No foreign materials such as animal faeces or fur were found in the samples. Significant differences were noted during sensory evaluation of cooked meals in different schools. The study showed that mid-day meal provided to the students fulfils the recommended daily requirement of a child, but there is a need to improve some of the contents of meal. For example, the fat content was low, and leafy vegetableswere deficient. There is a need to improve the quality and nutritional aspects of mid-day meal.